Pengaruh Prior Opinion, Debt Default dan Kondisi Keuangan terhadap Penerimaan Opini Audit Going Concern - Luthfi Alif Wibawa; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to provide empirical evidence regarding the effect of prior opinion, debt default, and financial condition on going concern audit opinion. The dependent variable is going concern audit opinion whose measurement is divided into four categories. While the independent variables are prior opinion, debt default, and financial condition. The prior opinion variable is measured by looking at the audit opinion in the previous year. The debt default variable is measured by considering the company's equity. The financial condition variable is measured by the zmijewski model. The research method was verifiable with a quantitative approach. This study uses logistic regression analysis to test the proposed hypothesis. The population in this study are companies in the infrastructure, utilities and transportation sectors that have been listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The results of this study indicate that prior opinion has a significant positive effect on going concern audit opinion, debt default and financial conditions have a positive but not significant effect on going concern audit opinion.